Gabor filter-based statistical features for ADHD detection - Sathiya, E.; Rao, T. D.; Kumar, T. Sunil (Frontiers in Human Neuroscience, 2024)
Attention Deficit/Hyperactivity Disorder (ADHD) is a neuropsychological disorder that occurs in children and is characterized by inattention, impulsivity and hyperactivity. Early and accurate diagnosis of ADHD is very important for effective intervention. The aim of this study is to develop a computer-aided approach to detect ADHD using electroencephalogram (EEG) signals. Specifically, we explore a Gabor filter-based statistical features approach for the classification of EEG signals into ADHD and healthy control (HC). The EEG signal is processed by a bank of Gabor filters to obtain narrow-band signals. Subsequently, a set of statistical features is extracted. The computed features are then subjected to feature selection. Finally, the obtained feature vector is given to a classifier to detect ADHD and HC. Our approach achieves the highest classification accuracy of 96.4% on a publicly available dataset. Furthermore, our approach demonstrates better classification accuracy than the existing methods.